Effect of immune activation on the kynurenine pathway and depression symptoms – A systematic review and meta-analysis. (November 2020) - Hunt, Charlotte; Macedo e Cordeiro, Thiago; Suchting, Robert; de Dios, Constanza; Cuellar Leal, Valeria A.; Soares, Jair C; Dantzer, Robert; Teixeira, Antonio L; Selvaraj, Sudhakar
Highlights: Interpheron-alpha treatment in patients with chronic medical illness was associated with a reduction in plasma tryptophan levels. Interferon-alpha treatment was associated with an increase in plasma kynurenine levels and kynurenine/tryptophan ratio activity. Interpheron-alpha treatment was associated with increase in depression symptoms over time. Abstract: Dysregulated kynurenine (KYN) pathway has been implicated in the pathophysiology of depression. In this systematic review, we examined the relationship between kynurenine pathway metabolites (KYN, kynurenic acid KYNA, tryptophan TRP, quinolinic acid QUIN, KYN/TRP ratio) and depression symptoms in the context of pro-inflammatory activation and immune response. Out of 5, 082 articles, fifteen studies were suitable; ten studies (N = 315 medically ill patients treated with interferon-alpha IFN-α) reported baseline and post-intervention plasma KYN, TRP and KYN/TRP ratios which were included in quantitative meta-analysis. Data from five studies were summarized (IFN-α, interferon-beta IFN-β, and lipopolysaccharide LPS). We found that IFN-α treatment in patients with chronic illnesses was associated with decreased TRP, increased levels of KYN and KYN/TRP ratio and depression scores from baseline to follow-up at both 4 and 24 weeks. Our findings suggest that increased risk of depression observed after immune-activating agents in patients with chronic medical illnesses is likely mediated by the kynurenine pathway. Further prospective studies are required to investigate the exact pathophysiology of the KYN pathway in depression.